The Effect Of Koya Reboned Powder Consumption On Protein Levels Of Pregnant Women In Prevention Of Stunting In Babies - Vera Iriani Abdullah (Jurnal Kesehatan Prima, 2021)
Linear growth retardation in childhood has decreased over the past few decades, but has not had a positive effect. In Indonesia, the change in the prevalence of stunting is around 37%. The nutritional status of pregnant women plays an important role in the incidence of stunting, which will be seen at the age of <5 years in 1000 days of their life. Pregnant women with poor nutrition and significant infection can give birth to a baby with stunting. For this reason, nutritional intake is needed, one of the animal foods that are high in protein is rebon shrimp about 62.4 g / 100 grams of dried shrimp. Protein has an important component so it is necessary for the physical development of children. The purpose of this study was to analyze serum protein levels before and after consuming rebon shrimp based PMT powder in the intervention group and control group and to analyze differences in serum protein levels for pregnant women before and after consuming PMT Koya powder made from rebon shrimp between the control and intervention groups. . This type of research is a quantitative study with a quasi-experimental method using the pre post test control group design approach. The number of respondents was 30 people who were divided into 2 groups, namely the intervention group and the control group. The intervention group was given koya powder as much as 100 grams / day for 7 days, assuming the fulfillment of 70 KKal. Data analysis using Data analysis using the Mann-Whitney test, if the data is not normally distributed. If the data are not normally distributed using the free sample t2 test. The conclusion of the analysis results to answer the research hypothesis. The results of the study were significant values P 0.000 <0.05. Conclusion There was a significant difference in serum protein levels of pregnant women before and after consuming PMT Koya powder made from boiled shrimp between the control and intervention groups.